coseca/coseca-1+coseca/coseca+1=2secsquareA
Answers
Answered by
5
✅cosecA/cosecA-1+cosecA/cosecA+1
✅=)cosecA(cosecA-1)+cosec(cosecA+1)
,,,,,,,( cosecA-1)(cosecA+1)
✅
=)cosec^2A-cosecA+cosec^2A+cosecA
✅,,,,,,,,,,,cosec^2A-1
✅=)2cosec^2A/cot^2A
✅=)2(1-cot^2A)/cot^2A
=)2tan^2A-2cot^2A/cot^2A
=)2tan^2A-2
RHS proved....
Answered by
15
⋆ ![\bold{\underline{\underline{\rm{\red{To\;Prove:-}}}}} \bold{\underline{\underline{\rm{\red{To\;Prove:-}}}}}](https://tex.z-dn.net/?f=%5Cbold%7B%5Cunderline%7B%5Cunderline%7B%5Crm%7B%5Cred%7BTo%5C%3BProve%3A-%7D%7D%7D%7D%7D)
⋆ ![\bold{\underline{\underline{\rm{\pink{Proof:-}}}}} \bold{\underline{\underline{\rm{\pink{Proof:-}}}}}](https://tex.z-dn.net/?f=%5Cbold%7B%5Cunderline%7B%5Cunderline%7B%5Crm%7B%5Cpink%7BProof%3A-%7D%7D%7D%7D%7D)
★ Taking L.H.S. :-
✦ LHS = RHS
Similar questions